Parent–child interaction during feeding or joint eating in parents of different weights. (August 2015) - Wendt, Verena; Bergmann, Sarah; Herfurth-Majstorovic, Katharina; Keitel-Korndörfer, Anja; von Klitzing, Kai; Klein, Annette M.
Abstract: The current study investigates parent–child interaction during feeding or during joint eating, and aimed to explore differences in feeding interactions between mothers and fathers, as well as between overweight, obese and not overweight parents. 148 mothers and 148 fathers with children aged between 7 and 47 months were observed during feeding of or joint eating with their child in the laboratory. The videotaped mother–child and father–child dyads were coded using the Chatoor Feeding Scale. This scale consists of 5 subscales: Dyadic Reciprocity, Dyadic Conflict, Talk and Distraction during Feeding, Struggle for Control, and Non-Contingency. Compared to mothers, fathers showed higher readings on the Talk and Distraction scale; in all other subscales no differences were found. The comparison between overweight, obese and not overweight mother–child dyads revealed no significant differences. Differences in father–child dyads between overweight, obese and not overweight fathers were identified in the subscale Struggle for Control: overweight fathers were marked by a higher amount of Struggle for Control than obese and not overweight fathers. Taken together, differences found in the present observational study are small to moderate, and thus the current results support extant literature demonstrating that there are no differences in feeding behaviour between mothers and fathers or between obese and non-obese parents. Highlights: We explore differences in feeding interactions between mothers and fathers of different weights. Differences found in the present observational study are small to moderate. Results support literature demonstrating no differences in feeding behaviour between mothers and fathers or parents of different weights.